Genesis of Moral Freedom in Kant - Rivera de Rosales, Jacinto (ETHICS IN PROGRESS, 2021)
In Kant’s writings, we can discover four key moments in the realization of moral freedom: i) The original possibility of being free, ii) The act described by Kant as radical evil, iii) The opposite act, that is, an inner conversion to good, and, finally, iv) The long process of the self-development of virtue extending to immortality. There are further issues such as the double concept of moral evil, and practical temporality. Moral freedom is originally located (and presupposed in Kant’s transcendental deduction) in the individual, her decisions, and the maxims or principles that guide her actions, even though a community (as both a „kingdom of ends” and social reality) provides the scope wherein all this takes place and its socially and historically-situated shapes. This paper tries to systematize these crucial stages of Kant’s moral philosophy with the focus on the concept of virtue.